Urbanization increases stochasticity and reduces the ecological stability of microbial communities in amphibian hosts - Zhou, Jin; Liao, Ziyan; Liu, Zhidong; Guo, Xuecheng; Zhang, Wenyan; Chen, Youhua (Frontiers in Microbiology, 2023)
Urbanization not only profoundly alters landscape profiles, ecosystems and vertebrate faunal diversity but also disturbs microbial communities by increasing stochasticity, vulnerability, biotic homogenization, etc. However, because of the buffering effect of host species, microbial communities are expected to be influenced by both host species and urbanization stresses. Therefore, the impacts of urbanization on animals’ microbial symbionts could be more complex and uncertain. In this study, we quantified the urbanization degree of sampling sites and surveyed the gut and skin microbes of three amphibian host species in different sites in urban parks and nearby villages of Chengdu, Southwest China. Furthermore, a co-occurrence network analysis, the phylogenetic normalized stochasticity ratio and Sloan neutral community models were applied to infer the impact of urbanization on symbiotic microbial communities. For the three host species, urbanization increased the diversity of symbiotic microbes and the number of keystone microbial taxa. However, the negative effects of such increased diversification were evident, as the community stochasticity and co-occurrence network structure vulnerability also increased, while the network structure complexity and stability were reduced. Finally, the community stochasticity had positive associations with the network vulnerability, implying that the existence of many transient symbiotic rare microbial taxa in urban parks makes the symbiotic microbial community structure more fragile. Conclusively, urbanization increased the symbiotic microbial diversity at the cost of community stability; the results provide a new perspective for better understanding the complex triangulated environment-host-microbe relationship.